PEMETAAN POTENSI BAHAYA BANJIR DI KABUPATEN MANOKWARI MELALUI PEMANFAATAN DATA GLOBAL PRECIPITATION MEASUREMENT (GPM) DAN ANALISIS BENTANG LAHAN - Arif Faisol; Indarto Indarto; Elida Novita; Budiyono Budiyono (The University of Lampung, 2020)
Rainfall data is the main parameter in flood analysis. The limited number of climate stations and rain stations in Manokwari due to low spatial representativeness of rainfall. This study aims to utilize Global Precipitation Measurement (GPM) as a satellite-based rainfall observer to analyze and floods hazard mapping in Manokwari. The method used in this research is landscape analysis. Research showed that almost all areas in Manokwari had high levels of flood hazard at any period except Tanah Rubuh district.